Pituitary carcinoma: A clinicopathological review - (:unkn) unknown (OXFORD UNIV PRESS INC, 2005)
PITUITARY CARCINOMAS ARE rare tumors; less than 100 well-documented cases have been reported to date. Such tumors are aggressive and associated with a high mortality rate. The molecular events leading to the development of pituitary carcinomas are largely unknown. Recent studies have only begun to shed light on the probable mechanisms of tumor initiation and progression. A review of the clinicopathological and molecular genetic characteristics of pituitary carcinomas is presented.
Keywords: diagnosis; genetics; metastasis; pituitary carcinoma; treatment; NEOPLASTIC HUMAN PITUITARIES; GENE-EXPRESSION; CORTICOTROPH CARCINOMA; TUMOR BEHAVIOR; ADENOMAS; METASTASES; GLAND; TUMORIGENESIS; INVASIVENESS; DISSEMINATION